Wisdom Related to Wild Edible Plants Consumption in Salung–Keelek Community, Mae Rim District, Chiang Mai Province - ใจเตี้ย , สามารถ; รัตนปัญญา, สิวลี; สุขสีทอง, ณัทธร; Pongchompoo, Sasikan; คำฟั้น, อัจฉรา (Journal of Health Science of Thailand, 2022)
The purposes of this mixed methods research were to collect the wisdom of the wisdom wild edible plants consuming database and predict influencing factors to people’s wild edible plants consumption. Altogether 301 households and 8 stakeholders in Saluang-Keelek community, Maerim District, Chiangmai Province were participated. Data were collected by documentary studies, questionnaires, non-structured interviews, and focus group discussion. Descriptive statistics, regression analysis and content analysis were used to describe the results. The results revealed that the wisdoms consuming wild edible plants could be divided into (1) seasonal quest, (2) recipes and consumption patterns, and (3) value adding of wild edible plants. The consumption of wild edible plants was low (mean=2.23±0.64). Only one variable significantly influenced to wild edible plants consumption of people was the forest resources conservation at 27.6% (p<0.05). In conclusion, the participants suggested to improve learning resources and utilization of wild edible plants knowledge through housewife community members. This would help to support the persistence of the wisdom on wild edible plants.